2018
DOI: 10.1161/circulationaha.117.031650
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Presentation and Perception of Symptoms Among Young Patients With Myocardial Infarction

Abstract: The presentation of AMI symptoms was similar for young women and men, with chest pain as the predominant symptom for both sexes. Women presented with a greater number of additional non-chest pain symptoms regardless of the presence of chest pain, and both women and their healthcare providers were less likely to attribute their prodromal symptoms to heart disease in comparison with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(136 citation statements)
references
References 28 publications
1
123
0
12
Order By: Relevance
“…Male gender is an independent cardiovascular risk factor and determines that cardiovascular disease develops at a younger age. On the other hand, the female gender is associated with a higher incidence of atypical symptoms and delays in diagnostic of cardiovascular conditions [ 22 , 23 ]. Overall, life expectancy is higher in women, but age-related comorbidities are also more prevalent [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male gender is an independent cardiovascular risk factor and determines that cardiovascular disease develops at a younger age. On the other hand, the female gender is associated with a higher incidence of atypical symptoms and delays in diagnostic of cardiovascular conditions [ 22 , 23 ]. Overall, life expectancy is higher in women, but age-related comorbidities are also more prevalent [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on younger patients, prospective cohort studies, such as GENESIS-PRAXY and VIRGO, have revealed some sex differences in demographic, CV risk factors, symptoms, and treatment. 77 , 78 Additionally, the social determinants of CVD in women have been much discussed, including health literacy, lower education, low-wage jobs, higher rates of poverty, and more familial responsibilities, coupled with societal discriminatory norms and practices. 40 …”
Section: Discussionmentioning
confidence: 99%
“… 81 Women often receive suboptimal CVD-preventive care. 78 A couple of years later, the Women’s Heart Alliance survey selected 200 primary-care providers and 100 cardiologists to determine their self-reported readiness to address CVD risk in women patients. Primary-care providers reported CVD as a principal health concern in women, yet less important than breast- and weight-related health.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian menunjukkan tidak ada hubungan di antara variabel tersebut (Alia et al, 2020). Namun studi lain menemukan hubungan antara rasio trigliserida/HDL dengan kadar Cystatin-C serum pada pasien DM Tipe 2 (Widyatmojo, 2019 (Lichtman, et al, 2018).…”
Section: Pendahuluanunclassified